(untitled) (ASEAN Engineering Journal, 2023)
Recently, the improvement and advancement in synthesizing nanoparticles via eco-friendly technique have been intensively explored since the used conventional physical and chemical methods always associated to the intensive energy usage and toxic waste pollution Therefore, nanoparticles synthesized from green route technique has initiate an interest among researchers due to its clean and eco-friendliness approach. In this study, the Fe doped TiO2 were synthesized using lawsonia inermis aqueous leaf extracts that act as reducing agent as well as capping and stabilizing agent. The green synthesized powder was then calcined and characterized using XRD, FESEM, EDX, FTIR and UV-Vis while photocatalytic activity was evaluated based on photodegradation efficiency of methylene blue (MB). The new obtained green calcined powder was found to have a crystalline phase (anatase structure) with crystallite size, 6.79 nm identified by XRD. The FESEM test shows the average particle size of the green synthesized calcined Fe doped TiO2 is in the range of 54.5 nm with capping agent (phyto-constituents) authorized by FTIR spectra. From EDX analysis, Fe ions was successfully incorporated into TiO2 compound during synthesis process confirmed by the presence of Fe element. It was observed that the band gap energy for green calcined Fe doped TiO2 is approximately 2.66 eV. The green synthesized calcined Fe doped TiO2 sample presented the highest photocatalytic activity efficiency under uv light irradiation for 3 hour which is 92.2% with only 7.8% of MB remained, this value is slightly higher than that of commercial P25 powder which is 90.7%. In conclusion, the green synthesis technique of using lawsonia inermis as natural resources as reduction agent was able to produce nanoparticles Fe doped TiO2. Moreover, the properties of Fe doped TiO2 nanoparticles has strong potential to be used as a photocatalyst since this sustainable green synthesis technique able to produce better nanoparticles properties as compared to conventional synthesis.